Polydatin attenuated neuropathic pain and motor dysfunction following spinal cord injury in rats by employing its anti-inflammatory and antioxidant effects - Bagheri Bavandpouri, Faezeh Sadat; Azizi, Atefeh; Abbaszadeh, Fatemeh; Kiani, Amir; Farzaei, Mohammad Hosein; Mohammadi-Noori, Ehsan; Fakhri, Sajad; Echeverría, Javier (Frontiers in Pharmacology, 2024)
Background: Considering the complex pathological mechanisms behind spinal cord injury (SCI) and the adverse effects of present non-approved drugs against SCI, new studies are needed to introduce novel multi-target active ingredients with higher efficacy and lower side effects.Polydatin (PLD) is a naturally occurring stilbenoid glucoside recognized for its antioxidative and anti-inflammatory properties. This study aimed to assess the effects of PLD on sensory-motor function following SCI in rats.Methods: Following laminectomy and clip compression injury at the thoracic 8 (T8)-T9 level of the spinal cord, rats were randomly assigned to five groups: Sham, SCI, and three groups receiving different doses of PLD treatment (1, 2, and 3 mg/kg). Over four weeks, behavioral tests were done such as von Frey, acetone drop, hot plate, Basso-Beattie-Bresnahan, and inclined plane, along with weight measurements. At the end of the study, changes in catalase and glutathione activity, nitrite level, activity of matrix metalloproteinase 2 (MMP2) and MMP9 as well as spinal tissue remyelination/neurogenesis, were evaluated.The results revealed that PLD treatment significantly improved the behavioral performance and weight of the animals starting from the first week after SCI. Additionally, PLD increased catalase, and glutathione levels, and MMP2 activity while reduced serum nitrite levels and MMP9. These positive effects were accompanied by a reduction in the size of the lesion and preservation of neuronal count.In conclusion, PLD showed neuroprotective effects in SCI rats by employing antiinflammatory and antioxidant effects, through which improve sensory and motor function.